Nivel de conocimientos y factores socioculturales maternos relacionados a la lactancia en niños menores de 6 meses. hospital eleazar guzmán barrón. nuevo chimbote, 2013 - Cueto Terrones, Génesis Melina (2014)
This research report, type descriptive, correlational Transverse section aimed to know the level of knowledge and sociocultural factors related to maternal breastfeeding in children under 6 months. Hospital Eleazar Guzman Barron, the sample consisted of 40 mothers who met the inclusion criteria. Level of maternal knowledge, maternal sociocultural factors and breastfeeding in children under 6 months: 3 instruments were used. The processing and analysis was performed in the statistical software: SPSS Data Editor Estatistics i8 test Chi square independence criteria. lt is concluded that: i. The 77.5% of mothers had an adequate level of knowledge and a level of 22.5% inadequate skills. 2. The 67.5% are 20 to 25 years old, 67.5% have a partner, 42.5% with secondary education, 42.5% are from urban area, 85.0% worked outside the home, 82.5% had complete prenatal and 85.0% have abad culture. 3. The 75.0% of mothers give exclusive breastfeeding and 25.0% provide mixed feeding mothers not to provide artificial feeding was found. 4. There is no statistically significant relationship between the level of maternal knowledge and breastfeeding in children under 6 months. 5. There is significant relationship between family ownership and work with breastfeeding. There was no statistically significant relationship between age, level of education, origin, culture prenatal and breastfeeding in children under 6 months.